Peptide vaccination induces profound changes in the immune system in patients with B-cell chronic lymphocytic leukemia - Michael Schmitt; Jacek Roliński; Anna Dmoszyńska; Paulina Własiuk; Krzysztof Giannopoulos (Folia Histochemica et Cytobiologica, 2011)
Although the immune status of chronic lymphocytic leukemia (CLL) patients is mostly characterized by immunosuppression, there is an accumulation of in vivo (graft-versus-leukemia effect) and in vitro (spontaneous remissions after infections) data that indicates that CLL might be effectively targeted by T-cell based immunotherapy. Recently, we characterized receptor for hyaluronic acid mediated motility (RHAMM) as a preferential target for immunotherapy of CLL. We also completed a RHAMM-derived peptide vaccination phase I/II clinical trial in CLL. Here, we present a detailed immunological analysis of six CLL patients vaccinated with HLA-A2 restricted RHAMM-derived epitope R3 (ILSLELMKL). Beside effective induction of R3-specific cytotoxic T-cells, peptide vaccination caused profound changes in different T-cell subsets as well as cytokines. We present longitudinal analyses of Th17, CD8+CD103+, CD8+CD137+ and IL-17 producing CD8+ T cells (CD8+IL- -17+) as well as important cytokines involved in regulation of immune response such as TGF-β, IL-10, IL-2 and TNF throughout the peptide vaccination period. (Folia Histochemica et Cytobiologica 2011, Vol. 49, No. 1, 161–167)